Analisis Faktor-faktor yang Memengaruhi Pola Pangan Harapan pada Rumah Tangga di Kelurahan Ngijo Kota Semarang - Reicilya, Mutiara Frida; Mukson, Mukson; Setiyawan, Hery (Universitas Galuh, 2024)
A diverse food composition indicates good quality in the consumption pattern of the community. Desirable Dietary Pattern (DDP) is an indicator to assess the nutritional quality and diversity of food consumption in the community, so that the results can be the basis for evaluation in building food security. This study aims to analyze the achievement level of DDP in households and analyze the factors that influence it. The research location is Ngijo Village, Gunungpati District, Semarang City. The research method used is a survey with quota sampling of 80 housewives. The data collection methods used are 2 x 24-hour food recall, interviews, and observations. Data analysis used are DDP analysis and multiple linear regression analysis. The results showed that Ngijo Village had a DDP score of 85,07 and was classified as a good category in describing the diversity and quality of household food consumption patterns in it. Simultaneously, the variables of household income, number of household members, education of housewives, age of housewives, land utilization, and nutritional knowledge of housewives have an influence on the DDP score. While partially, the variables that influence the DDP score are household income, housewife education, and housewife nutritional knowledge.